1997
DOI: 10.1128/iai.65.1.55-63.1997
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of recombinant transferrin-binding protein B variants from Neisseria meningitidis for their ability to induce cross-reactive and bactericidal antibodies against a genetically diverse collection of serogroup B strains

Abstract: Transferrin-binding protein B (TbpB) is a surface-exposed protein, variable among strains of Neisseria meningitidis, that has been considered as a vaccine candidate. To define a TbpB molecule that would give rise to broadly cross-reactive antibodies with TbpB of many strains, specific antisera were produced against three recombinant TbpB variants from strain M982: one corresponding to the full-length TbpB; one in which stretches of amino acids located in the central part of the molecule, described as hypervari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(38 citation statements)
references
References 55 publications
(91 reference statements)
1
36
0
1
Order By: Relevance
“…The data demonstrate for the first time the presence of the TonB region in H. parasuis and that the proteins encoded by these genes are upregulated under iron-poor conditions. It also proved possible to show that the N-terminus domain of the H. parasuis TbpB protein is an immunodominant region, similar to what has been reported for the N-terminal domain of Neisseria meningitidis TbpB protein [12].…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…The data demonstrate for the first time the presence of the TonB region in H. parasuis and that the proteins encoded by these genes are upregulated under iron-poor conditions. It also proved possible to show that the N-terminus domain of the H. parasuis TbpB protein is an immunodominant region, similar to what has been reported for the N-terminal domain of Neisseria meningitidis TbpB protein [12].…”
Section: Introductionsupporting
confidence: 78%
“…The detection and production of a soluble and purified form of H. parasuis recombinant TbpB-His, that is likely to be surface accessible to antibodies, provides an opportunity to directly assess whether this antigen can serve as an effective vaccine antigen to protect not only against serotype specific H. parasuis, but also against other serotypes of H. parasuis. Previous experiments immunizing with recombinant TbpB from N. meningitidis [12] have shown that the antibodies generated against the N-terminus domain were sufficient to develop an efficient immune response against the infection by this microorganism.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to antibiotic resistance, where extensive spread has resulted due to the use of antibiotics in animal husbandry and for treatment of disease, the stimulation of long-lasting, effective antibodies will favour the growth of recombinants that can evade protective antibodies. Immunization of experimental animals with members of each TbpB family has yielded antibodies that are bactericidal against other members of the same family but less effective or only poorly bactericidal against members of the other families (Rokbi et al, 1997b). A lack of cross-reactivity between the families could also explain why most of the imported tbpB alleles in subgroups IV-1 and III belonged to a different family than did the ancestral tbpB1 allele.…”
Section: Discussionmentioning
confidence: 99%
“…), 10 and 101 (both found in N. lactamica), as well as 25 other novel alleles in families 1, 3 and 4. Genetic variation of tbpB within the ET5 complex of serogroup B meningococci has also been reported (Rokbi et al, 1997b). Thus, import of tbpB has occurred in several clonal groupings and epidemiological situations, albeit at frequencies that differ with the clonal grouping for reasons that are not understood.…”
Section: Other Clonal Groupingsmentioning
confidence: 93%
“…It is thought that the major defence against meningococci consists of antibodies that are able to induce the bactericidal activity of the complement system (Goldschneider et al, 1969). Antibodies raised in mice or rabbits were both bactericidal and cross-reactive in some cases (Ala'Aldeen and Borriello, 1996;Rokbi et al, 1997). The TbpB protein seems to be more efficient in generating this response than the TbpA protein.…”
Section: Figmentioning
confidence: 99%